Teaching for student learning : - Ryan, Kevin (Cengage, 2013)
To accommodate the evolution of teacher education programs, this text has been developed for two groups: 1) those serving as interns or student teachers as they complete traditional teacher education programs and 2) new in-service teachers who are part of an alternative certification program. The book's team of experienced educators and authors offers users a set of very practical tools, skills, and advice that they can put into immediate use in the field. The authors also aim to provoke a high level of engagement and interaction with the program. TEACHING FOR STUDENT LEARNING features a reader-friendly style and a convenient format with three-hole punched, perforated pages. This convenient format, along with the book's 25 brief, to-the-point chapters (modules), makes it easy for busy teachers to quickly find, understand, and use key information related to their most pressing needs.